Bloom, Lisa E., (2022) Climate Change and the New Polar Aesthetics: Artists Reimagine the Arctic and Antarctic. - Patranobish, Paromita (Journal of Ecohumanism, 2023)
This review critically examines Lisa E. Bloom’s Climate Change and the New Polar Aesthetics (2022) by studying the bookâ€™s key methodological and analytical approaches to contemporary visual art on the poles. I locate Bloom’s work as part of a larger discourse on Ice Humanities and highlight her own contribution to the field by focusing on the book’s reconfiguration of critical environmentalism through intersectional feminist, indigenous, and transnational frameworks. The review also discusses the dual role of aesthetics in both shaping hegemonic perceptions of the poles and in articulating strategies for their subversion.